Perlindungan Hukum Terhadap Korban Child Cyber Grooming Dalam Kejahatan Seksual - Mediol Stiovanny Yoku (LAW Proscientist: Journal of Law Profesional Scientist, 2022)
The purpose of this research is to know and understand, and to analyze what factors are dominating in order to find out the form of regulation of child cyber grooming in sexual crimes in Indonesia, and to know and understand, and to analyze what efforts need to be implemented in order to legal responsibility for perpetrators of child cyber grooming in sexual crimes in Indonesia. This type of research is normative legal research. The author uses three approaches, including statutory approach, conceptual approach, and comparative approach. Forms of child sexual crimes using technology can be categorized in several forms, namely child sexual abuse/exploitation material, online grooming for sexual purposes, sexting, sexual extortion, and live online child sexual abuse. These forms of sexual crimes against children are found almost all over the world so there is an urgency to overcome them so that children who are the future of the nation are not damaged both physically and mentally and morally from an early age.